Key Largo [videorecording (DVD)] - Brooks, Richard, 1912-1992; Huston, John, 1906-1987; Bogart, Humphrey, 1899-1957; Robinson, Edward G., 1893-1973; Bacall, Lauren, 1924-2014; Barrymore, Lionel, 1878-1954; Trevor, Claire, 1910-2000; Anderson, Maxwell, 1888-1959 (Turner Entertainment Co. ; Warner Home Video, 2000)
A disillusioned returning World War II veteran has lost the will to fight ... until he arrives at a rundown hotel in Key Largo. There a mobster holes up against a raging storm, holding the veteran, the hotel owner and the owner's widowed daughter-in-law at gunpoint.